Living Storytelling as an Impetus for Organizational Change:: Towards Connective Observing and Writing - Maas, Alexander (Narrative Matters, 2012)
This paper examines how to use storytelling as impetus for organizational change. A saying goes that “lasting change starts with me, not with someone else.” The problem of many change processes is that a change agent writes a change report but the actual implementation by actors in the organization fails. The question becomes how a researcher can relate to participants in an organization in such a way that the change process becomes their process. For many change agents, storytelling is a powerful way for exploring an organizational setting and for putting ideas into an organization. In this paper, I elaborate some aspects of a relational inquiry stand (McNamee & Hosking, 2012), in which I use storytelling as an intervention method. As a consequence, participants are activated; “connective observing” and “connective writing” emerge. It opens the possibility for multi-layeredness and “living storytelling.” Will the researcher and active participants in the change process exchange positions?